Comparison of three malnutrition screening tools prior to allogeneic hematopoietic stem-cell transplantation - Khosroshahi, Reza Amiri; Mohammadi, Hamed; Barkhordar, Maryam; Zeraattalab-Motlagh, Sheida; Imani, Hossein; Rashidi, Amirabbas; Sadeghi, Erfan; Wilkins, Simon; Mousavi, Seyed Asadollah (Frontiers in Nutrition, 2023)
Previous studies have shown that malnutrition before hematopoietic stem cell transplantation (HSCT) is associated with poor patient prognoses. There is inconsistency among studies on which nutritional status screening tool is appropriate for malnutrition diagnosis before allo-HSCT. The present study aimed to compare nutritional screening tools in patients with leukemia before allo-HSCT. An observational, cross-sectional, and single-center study was conducted in Tehran, Iran.One hundred four adults allo-HSCT candidates aged 18-55 years with leukemia were selected sequentially. Malnutrition assessment was done using three tools, the Global Leadership Initiative on Malnutrition (GLIM), nutritional risk screening 2002 (NRS-2002) and European Society for Clinical Nutrition and Metabolism (ESPEN) criteria. The agreement between malnutrition assessment tools was evaluated with Cohen's kappa. The agreement between GLIM and NRS-2002 was perfect (=0.817, P<0.001), while the agreement between GLIM and ESPEN was fair (=0.362, P<0.001). The agreement between NRS-2002 and ESPEN was fair (=0.262, P<0.001).We also found a moderate agreement for all tools (=0.489, P<0.001). NRS-2002 is an accepted tool for screening malnutrition in hospitalized patients. In the current study, the GLIM criterion perfectly agreed with the NRS-2002. Further studies in the HSCT setting are needed to introduce a valid tool.